The Influence of Service Quality on Customer Satisfaction Using the Banking Service Quality (BSQ) Method - Hidayat, Rahmad; Tosungku, La Ode Ahmad Safar; Pawitra, Theresia Amelia (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
This study aims to analyze service quality at Bank ‘X’ by applying the Banking Service Quality (BSQ) method. Service quality is a crucial factor in maintaining customer satisfaction and preserving the bank's competitiveness against other banks. The BSQ method is used to identify the dimensions of service quality that have the most influence on customer perceptions of services at Bank ’X’. This research employs a quantitative approach by collecting data through questionnaires distributed to customers of Bank ‘X’, the collected data are then analyzed using statistical techniques such as factor analysis to identify service quality variables that emerge from customer perceptions. Additionally, regression analysis is conducted to measure the influence of each dimension on customer satisfaction. The results of this research indicate a negative gap in the access variable, while the other variable experience a positive gap. Negative gap results are also found in the attributes of "customer service assistance," "number of tellers and customer service staff," and "queues at tellers and customer service." The Pearson product-moment correlation test results show that all variables are related to customer satisfaction. The influence of service quality on customer satisfaction at Bank ‘X’ is represented by the equation Y = -5.708 + 0.290X1 + 0.305X2 - 0.423X3 + 0.422X3 + 0.341X5 + 0.35X6. The results of the F-statistic test indicate that all service quality variables significantly influence customer satisfaction simultaneously. The t-statistic results reveal that the reliability variable does not have a significant partial effect on customer satisfaction, whereas the other variable have a significant partial effect on customer satisfaction.